Transdisciplinary breastfeeding support: Creating program and policy synergy across the reproductive continuum - Labbok Miriam H (BMC, 2008)
Abstract This paper was presented at the symposium on Breastfeeding and Feminism: A Focus on Reproductive Health, Rights and Justice. It underscores the power and potential of synergy between and among organizations and individuals supporting breastfeeding, the mother-child dyad, and reproductive health to increase sustainable breastfeeding support. These concepts were brought together to lay the groundwork for working group discussions of synergy in program and policy actions.